Ancillary studies on cell blocks from fine needle aspiration specimens of salivary gland lesions: A multi‐institutional study. Issue 5 (29th January 2022) - Tabibi, Seena; Gabrielson, Matthew; Saoud, Carla; Davis, Katelynn; Wangsiricharoen, Sintawat; Lu, Ryan; Tondi Resta, Isabella; Viswanathan, Kartik; Faquin, William C.; Baloch, Zubair; Maleki, Zahra
Abstract: Background: Ancillary studies are commonly performed on cell blocks prepared from fine‐needle aspiration (FNA) specimens. There are limited studies in application of ancillary studies on cell blocks from salivary gland (SG) FNAs. This multi‐institutional study evaluates the role of ancillary studies performed on cell blocks in the diagnosis of SG lesions, and their impact on clinical management. Method: The electronic pathology archives of three large academic institutions were searched for SG FNAs with ancillary studies performed on cell blocks. The patient demographics, FNA site, cytologic diagnosis, ancillary studies, and surgical follow‐up were recorded. If needed, the cytologic diagnoses were reclassified as per the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC). Results: 117 SG FNA cases were identified including 3, 10, 11, 6, 23, 4, and 60 cases in MSRSGC categories I, II, III, IVa, IVb, V, VI, respectively with surgical follow‐up available ranging from 27% to 100% within each category. Ancillary studies including histochemistry, immunocytochemistry (IHC), and in situ hybridization (ISH) were beneficial in 60%–100% of cases in each category. Risk of malignancy was 100% in both the suspicious for malignancy (V) and malignant (VI) categories. Ancillary studies improved diagnosis in 60% of non‐neoplastic cases (II, 6/10), 100% of benign neoplasm cases (IVa, 6/6), and 98.3% of malignant cases (VI, 59/60). Conclusion: Judicious and case‐based ancillary studies performed on SG FNA cell blocks with sufficient material can improve the diagnostic yield by further characterization of the atypical/neoplastic cells, particularly in MSRSGC categories IVa‐VI.